Pemantau Suhu dan Kadar Air Kompos Berbasis Internet Of Things (Iot) dengan Arduino Mega dan Esp8266 - Putu Gede Budisanjaya; I Wayan Tika; Sumiyati (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2016)
In composting process, temperature and water content are specific thus needs to be monitoredcontinuously. The objective of this study was to monitor temperature and moisture content in realtime during the process of straw and chicken manure composting. This device combined withInternet technology called the Internet of Things (IOT) and consist of Arduino Mega 2560 board,DS18B20 temperature sensor, resistive based moisture content probe with IC 555 as the currentexcitation. The results of the temperature and moisture content displayed on the LCD 4x20 andcan be seen online at sites thingspeak.com because transmitted by ESP8266 wifi module. Datatemperature and moisture content of compost material was also stored to the sd card